Erotic elevation: Exploring the psychological and cultural dimensions of sexual imagery carved on tudals of temples of kathmandu valley - Adhikary, Ramesh Prasad (Universidad de las Regiones Autónomas de la Costa Caribe Nicaragüense - URACCAN, 2025)
Hindu temple art in the Kathmandu Valley of Nepal is renowned for its intricate carvings, particularly the tudals—wooden roof struts—that often depict gods and goddesses in explicit sexual poses. These carvings, deeply rooted in Tantric traditions, symbolize fertility, cosmic unity, and spiritual transcendence. Despite their cultural and historical significance, there remains a paucity of psychological research on their impact. This study employs a multidisciplinary approach integrating historical, cultural, and psychological perspectives to explore the implications of these carvings. Historical and cultural analyses reveal their origins in Tantric practices, where sexual symbolism signifies the union of opposing forces to achieve enlightenment. Mythologically, the carvings depict divine unions like Shiva and Shakti, embodying profound spiritual concepts. Culturally, the Newar community views these carvings not as taboo but as sacred representations of life’s vitality and divine blessings. Symbolically, they denote the integration of dualities and the cyclical nature of existence, which is crucial for spiritual growth. Psychologically, Freudian and Jungian frameworks elucidate how these carvings serve as outlets for repressed desires and facilitate individuation by integrating unconscious elements. This research synthesizes existing literature and conducts archival research to contextualize these carvings within their historical and religious frameworks. It also employs thematic analysis to uncover their symbolic meanings and uses of psychological theories to interpret their impact on worshippers and visitors. By bridging gaps in existing scholarship, this study aims to deepen our understanding of Nepali temple art’s psychological dimensions. It underscores the importance of these carvings not just as aesthetic artifacts but as profound expressions of spirituality and cultural identity. Ultimately, this research contributes to broader conversations at the intersection of sexuality, spirituality, and cultural heritage, highlighting the enduring relevance and significance of these ancient artistic traditions in contemporary society.